Factors Affecting Intention to Use E-Learning Systems in Selected Universities in Phnom Penh, Cambodia - Try, Sothearith; Daengdej, Jirapun; Vongurai, Rawin (ABAC ODI JOURNAL Vision. Action. Outcome, 2022)
This research investigates factors influencing the intention to use e-learning systems in selected universities in Phnom Penh, Cambodia. The conceptual framework has been developed by adopting previous theoretical studies and research models of the modified unified theory of acceptance and use of technology (UTAUT2). Five hundred questionnaires were collected from undergraduate students through Google form survey with universities’ administration assistance. Multi-stage sampling was used: the first stage is stratified random sampling followed by purposive sampling. Collected data were analyzed using the Structural Equation Model (SEM) and Confirmatory Factor Analysis (CFA) to confirm the model fit and hypothesis testing. The findings showed that performance expectancy, effort expectancy and self-efficacy did not have any influence on behavioral intention. However, social influence had the strongest influence on behavioral intention to use e-learning systems, followed by facilitating conditions. Moreover, facilitating conditions and behavioral intention had a significant influence on use behavior of e-learning systems. This study provided theoretical implications for researchers related to technology adoption and information for training institutions, universities, schools and academic staff on issues they need to focus on when they wish to launch any new system or online services.